Towards better child protection programmes: a qualitative evaluation of Youth Disseminating Life Skills Programme - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
The present study aimed to assess the acceptability of a 12-week training programme, Youth Disseminating Life Skills Programme whose aims were to help university students acquire knowledge on and to increase sensitivity towards child abuse and neglect by adopting a qualitative methodology. The sample consisted of 13 university students who took part in the Youth Disseminating Life Skills Programme (10 female, 3 male: mean age 22 years; age range: 20-31). With the help of a general interview guide, the focus group meetings were held. Established conventions guided the analysis. Participants recounted feelings about and benefits of the Programme, and ways to improve the Programme. Feelings about the Programme included both positive (e.g. feeling hopeful) and negative feelings (e.g. feeling traumatised). Participants recounted a variety of benefits of the Programme (e.g. correcting some myths about child abuse). Participants proposed some ways whereby the Programme could be improved. Some findings could be interpreted in terms of existing literature/theory. Other findings extended the literature and could be viewed as targets for future child protection programmes.
Keywords: Child abuse and neglect; qualitative research; focus groups; RANDOMIZED-TRIAL; PREVENTION; ABUSE